RASIO KEUANGAN, MAKROEKONOMI DAN FINANCIAL DISTRESS: STUDI PADA PERUSAHAAN PERDAGANGAN, JASA DAN INVESTASI DI INDONESIA - PRIYATNASARI, SHEILLA; HARTONO, ULIL (Jurnal Ilmu Manajemen (JIM), 2019)
Financial distress causes bankruptcy if happens continuously, so the company need an anylisis to detect some factor that influence it. This research aims to determine the factors that affect financial distress company in trade, services and investment sector. The predictor that use in this study is financial ratio include return on assets, return on equity, current ratio, debt to assets ratio, total assets turnover, and also macroeconomics (inflation and interest ratio) to predict the financial distress condition. This study uses an assosiative causal approach and the data used in in the secondary data. The object used in this study is trade, services and investment sector companies listed in Indonesia Stock Exchange at the period 2013-2017. The sample of this study was 71 companies. Data analysis technique used is logistic regression. The result show that ROA and DAR give negatively affect on financial distress, and other variables of return on equity, current ratio, total assets turnover, inflation and interest rate does not affect on financial distress. Therefore, the companies are expected to pay attention the value of return on assets and debt to assets ratio for avoid the probability of financial distress. Keywords: company; financial dsitress; financial ratio; inflation; interest rate.